Stem cell therapy for cardiovascular disease: the demise of alchemy and rise of pharmacology. (25th April 2013) - Jadczyk, T; Faulkner, A; Madeddu, P
<x xml:space="preserve">Abstract</x> Regenerative medicine holds great promise as a way of addressing the limitations of current treatments of ischaemic disease. In preclinical models, transplantation of different types of stem cells or progenitor cells results in improved recovery from ischaemia. Furthermore, experimental studies indicate that cell therapy influences a spectrum of processes, including neovascularization and cardiomyogenesis as well as inflammation, apoptosis and interstitial fibrosis. Thus, distinct strategies might be required for specific regenerative needs. Nonetheless, clinical studies have so far investigated a relatively small number of options, focusing mainly on the use of bone marrow‐derived cells. Rapid clinical translation resulted in a number of small clinical trials that do not have sufficient power to address the therapeutic potential of the new approach. Moreover, full exploitation has been hindered so far by the absence of a solid theoretical framework and inadequate development plans. This article reviews the current knowledge on cell therapy and proposes a model theory for interpretation of experimental and clinical outcomes from a pharmacological perspective. Eventually, with an increased association between cell therapy and traditional pharmacotherapy, we will soon need to adopt a unified theory for understanding how the two practices additively interact for a patient's benefit. LINKED ARTICLES This article is part of a themed section on Regenerative Medicine and Pharmacology: A Look to the Future. To view the other articles in this section visit http://dx.doi.org/10.1111/bph.2013.169.issue-2